Master-proxy host structure for efficient document retrieval - Soh, Ying Kwang. (2008)
This project involves the development of an E-learning master-proxy system for the hosting and retrieval of E-learning documents. eavily accessed documents are dynamically distributed via mobile agents to proxy hosts surrounding the main E-learning server. Some of the heavy traffic can then be re-routed away from the central server, easing the bottleneck. The faded information field layer structure method was studied and verified. The response time of this method is observed, analysed and compared to traditional method. It was found that there is significant improvement in response time. This dissertation concludes by suggesting additional experimental works and tests for refining the system.